2019
DOI: 10.1080/17461391.2019.1664639
|View full text |Cite
|
Sign up to set email alerts
|

Step length and grade effects on energy absorption and impact attenuation in running

Abstract: We sought to examine the effect of step length manipulation on energy absorption and impact attenuation during graded running. Nineteen runners (10F, 9M) ran on an instrumented treadmill at three step lengths (preferred and ±10% preferred) at each of five grades (0°, ±5°, and ±10°) while 3D motion data were captured. Speed was held constant at 3.33 m/s and step length was manipulated by syncing cadence to a metronome. Manipulating step length altered energy absorption (p ≤ 0.002) and impact attenuation (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…We analyzed a pre-existing dataset (Baggaley et al, 2019;Khassetarash et al, 2020;Vernillo et al, 2020) where 21 subjects ran at a combination of running speeds and slopes. Two subjects were excluded from the current analysis due to equipment data acquisition errors, leaving 19 subjects remaining (10 Male, 9 Female; 29 ± 9 years, 173 ± 9 cm, 68.1 ± 9.9 kg).…”
Section: Subjectsmentioning
confidence: 99%
“…We analyzed a pre-existing dataset (Baggaley et al, 2019;Khassetarash et al, 2020;Vernillo et al, 2020) where 21 subjects ran at a combination of running speeds and slopes. Two subjects were excluded from the current analysis due to equipment data acquisition errors, leaving 19 subjects remaining (10 Male, 9 Female; 29 ± 9 years, 173 ± 9 cm, 68.1 ± 9.9 kg).…”
Section: Subjectsmentioning
confidence: 99%
“…rear-, mid-and fore-foot) can influence the mechanical strain applied to lower limb muscles during running [214][215][216][217]. Accordingly, manipulating foot stride frequency [218] and foot strike pattern [219] during DR could reduce EIMD including neuromuscular fatigue. Following an intermittent 45-min treadmill DR (9 × 5-min; slope: − 15%; speed: 10.5 km h −1 ), Rowlands et al [68] reported lower MVC torque decrements post-DR using an understride strategy (− 8.8% MVC torque; 92% preferred stride length) compared with an overstride (− 14.7% MVC torque; 108% preferred stride length) or preferred stride strategy (− 15.5% MVC torque).…”
Section: Optimisation Of Stride and Foot Strike Patternmentioning
confidence: 99%
“…3 a Schematic representation of the time course of alterations following downhill running (DR) and b current scientific evidence on the benefits of different adaptation strategies to DR (i.e. prior exposure to DR [ 46 , 63 , 67 , 68 , 85 , 92 , 121 , 141 , 143 , 165 , 181 , 184 , 185 , 192 , 193 , 196 , 197 ], preconditioning strategies [ 16 , 81 ], DR training [ 14 , 209 , 210 , 254 ], changes in stride pattern [ 32 , 67 , 68 , 218 , 219 , 221 , 220 , 228 , 255 ], the use of lower limb compression garments [ 15 , 236 , 237 ], and the use of specific footwear [ 28 , 149 , 253 , 256 ]. In a and b , orange, blue, red, purple, and green spheres correspond to isometric MVC force/torque loss, changes in running economy and mechanics, ultrastructural alterations, inflammation and oedema, and muscle soreness, respectively.…”
Section: Factors Influencing the Magnitude Of Muscle Damage Followingmentioning
confidence: 99%
See 2 more Smart Citations